The Upside of Anger - Binder, Mike, 1958-; Allen, Joan, 1956-; Costner, Kevin; Christensen, Erika, 1982-; Wood, Evan Rachel, 1987-; Russell, Keri, 1976-; Witt, Alicia, 1975- ([United States] : New Line Home Entertainment, 2005)
Terry Wolfmeyer is a sharp-witted suburban wife who is left alone to raise her four headstrong daughters when her husband unexpectedly disappears. Things get even more hectic around their house when Terry falls for her neighbor Denny, a once-great baseball star turned local radio D.J. This leaves her daughters out on a limb because now they have to juggle their own romantic ups and downs as well as having to deal with the dilemmas of their mom.
Special features: Commentary with director Mike Binder, Joan Allen and moderated by filmmaker Rod Lurie; deleted scenes with commentary by director Mike Binder; 30-minutes documentary; theatrical trailer.
New DVD 2024 Winter.
Produced by Alex Gartner, Jack Binder, Sammy Lee ; written and directed by Mike Binder.
DVD, region 1, widescreen (2.35:1) presentation; Dolby Digital 5.1 surround, Dolby Digital 2.0 stereo.
English dialogue, English or Spanish subtitles; closed-captioned.
Keywords: Drama films